PENERAPAN STANDAR RESEP DALAM PEMBUATAN PRODUK PASTRY DI HOTEL ROYAL ASNOF PEKANBARU - Eka Octaviani; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Hospitality is one of the tourism sectors that provides facilities in the field of services which include food accommodation and entertainment. Food beverage product is one of the sections in hotels that focuses on providing food, one of which is pastry with various cakes that have standar recipes, Standar recipes are benchmarks for achievement based on at the level of best desire which is used as a comparison to achieve the degree that is considered the best The research will be carried out at the Royal Asnof Hotel Pekanbaru, this hotel was chosen as a place of research to find out how the application of standar recipes in the manufacture of pastry products at Royal Asnof Hotel Pekanbaru is in accordance with professional standars This study uses a qualitative method with a descriptive approach, data collection techniques in this study use documentation observation, interviews so that a clear picture can be obtained of the object under study and can be used. Conclusion Based on the research shows that the application of standar recipes in the manufacture of pastry products at the Royal Asnof Hotel, Pekanbaru is in the bad category and has not been in accordance with the professional good standars of the application of recipe standars Keywords : Standar Recipes, Pastry, Cake, Hotel